Contribution to the knowledge of the oribatid mite genus Eutegaeus (Acari, Oribatida, Eutegaeidae) - Ermilov, Sergey G. (Zootaxa, 2020)
The genus Eutegaeus (Oribatida, Eutegaeidae) comprises 13 species, which are distributed in the Australian, Neotropical and Antarctic regions; of these, two new species are described from litter in the relictual Valdivian forest of Chile. Eutegaeus parapapuaensis sp. nov. (description based on the adult and tritonymph) differs from Eutegaeus papuensis Aoki, 1964 by the absence of translamella, interbothridial tubercles, notogastral setae h3 and epimeral setae 3a. Eutegaeus paralagrecai sp. nov. (description based on the adult and proto-, deuto- and tritonymph) differs from Eutegaeus lagrecai Arcidiacono, 1993 by the presence of lanceolate bothridial setae and long notogastral setae p1, and the absence of striate ornamentation on the notogaster. A revised generic diagnosis and an identification key to known species of Eutegaeus are presented. Nymphs of Eutegaeus and related genera in Eutegaeoidea are compared.